Visual Rhythm in Krishna Prakash Shah’s Abstract Paintings - Sharma, Yam Prasad (SCHOLARS: Journal of Arts & Humanities, 2021)
Krishna Prakash Shah's abstract paintings present visual rhythm in the canvas that provides a sensation of music, melody and motion. Lines, colors and shapes are running and flowing in a spontaneous manner as fluid without any obstacle on their way. Due to harmony and cohesion among colors and shapes, the visual compositions create a friendly atmosphere and comfort to our eyes. The artworks have such a power that invites the viewers to enter the canvas and explore the unknown world, having an adventurous imaginary journey. The viewers become the characters who travel back and forth along with the swinging shapes and lines. Due to the aesthetic experience of visual rhythm, the viewers become the one with the viewed artwork. The distance between the subject and the object is lost since the viewers assimilate with the artwork. The dynamic lines, colors and shapes are flowing spontaneously. This motion and flow suggest the visual melody and music. The scope of the study includes Krishna Shah's abstract paintings which have been explored from the perspective of visual rhythm and music as a tool for interpreting artworks. The study is qualitative since the artworks have the possibility of multiple interpretations. This paper, thus, attempts to trace the visual rhythm in his abstract compositions and their aesthetic values.